Fabrication of Mo-encapsulated stainless steel by powder metallurgy and assessment of localized corrosion resistance - Haruka Saito; Masashi Nishimoto; Izumi Muto (Journal of Materials Research and Technology)
As a source of corrosion inhibitors, 2.5% Mo powder was mixed with Type 304L stainless steel powder and spark-plasma sintered to a fabricate Mo-encapsulated Type 304L stainless steel. The Mo particles formed a core/shell structure. The localized corrosion resistance of the fabricated Mo-encapsulated Type 304L stainless steel was compared with those of spark-plasma-sintered Type 304L and Type 316L stainless steels. Potentiodynamic polarization in 0.1 M NaCl suggested that the Mo cores could release molybdate, which acts as an inhibitor. However, the shells did not dissolve, preventing the Mo-enriched particles from acting as pit initiation sites. Similarly, the surface of the Mo core dissolved during dip-and-dry cycles using 0.1 M NaCl, but the shell was less prone to dissolution. Although the fabricated Mo-encapsulated stainless steel did not contain Mo as a solid solution, its rust resistance was equivalent to that of spark-plasma-sintered Type 316L stainless steel. In potentiodynamic polarization, the initiation potential for localized corrosion of the Mo-encapsulated Type 304L stainless steel was remarkably higher than those of the sintered Type 304L and Type 316L stainless steels. The corrosion inhibition mechanism of the Mo-encapsulated Type 304L stainless steel was discussed from three viewpoints: (1) passive film modification on the steel matrix, (2) cathodic protection of the steel matrix by the Mo core dissolution, and (3) corrosion inhibition by molybdate dissolved from the Mo-enriched particles, and the last one appeared to be the most likely.